PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN PAI KELAS IX DI UPTD SMPN 2 KECAMATAN BUKIK BARISAN - Adeng Putra; Zulfani Sesmiarni; Rodi Rodi; Deki Putrama Al-Khairi (CV. ADIBA AISHA AMIRA, 2024)
This study aims to analyze the improvement of student learning outcomes in Islamic Religious Education (PAI) subjects through the use of audio-visual media at UPTD SMPN 2, Bukik Barisan District. The method used is an experiment with a quantitative approach, involving two groups of grade IX students, namely the control group and the experimental group. The results of the study showed that the use of audio-visual media significantly increased students' understanding and interest in PAI materials. Data analysis was carried out using pretest and posttest tests, which showed an increase in the average score of students in the experimental group compared to the control group. These findings recommend the integration of audio-visual media in the learning process to improve the quality of education, especially in teaching PAI.